The Knowledge Management Model to Support Academic Activities at SD Al-Imam Islamic School Cileungsi Using the Seci Approach - Bajsair, Faik; Pranoto, Gatot Tri (Universitas Trilogi, 2023)
The absence of a processing model, knowledge storage due Knowledge in the form of notes, files, pictures and so on disappears because 17 teachers dump themselves and bring knowledge, files, notes that ever made. Allegedly with the creation of a processing model, knowledge-based storage a website with a SECI approach can provide a managed solution with good knowledge at SD Al-Imam Islamic school.